PENGARUH LEVERAGE, UKURAN PERUSAHAAN DAN DEWAN KOMISARIS INDEPENDEN TERHADAP NILAI PERUSAHAAN - Eki Kustiawan Haris (2021)
This research is a quantitative study that aimed to examine the effect of leverage as measured by DER, firm size as measured by Ln total assets and independent board of commissioners as measured by the division between the number of independent commissioners and the number of company commissioners on firm value. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange and the websites of each company for the 2017-2019 period which were selected using the probability sampling method. Hypothesis testing in this study used Multiple Linear Regression Analysis with SPSS program and a significance level of 0.05. The test results show that (1) leverage has a significant positive effect on firm value (2) firm size has no effect on firm value (3) independent board of commissioners has no effect on firm value.